2004
DOI: 10.1080/09637480310001642510
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum(‘Lingzhi’); acute and short-term biomarker response to supplementation

Abstract: Ganoderma lucidum (Lingzhi) is a popular Chinese herb with an impressive array of reputed health benefits, including antioxidant properties. However, these require scientific validation. The aim of this study was to investigate in vitro antioxidant capacity of Lingzhi, absorption and systemic distribution of Lingzhi antioxidants, and effects of short-term (10 days) supplementation on biomarkers of antioxidant status, coronary heart disease (CHD) risk and DNA damage. In this double-blinded, placebo-controlled, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 16 publications
3
34
0
Order By: Relevance
“…10,14,15,17,20,25,60,74,75,111,127,143,155,166,171,172). Halvorsen et al presented the total antioxidant (redox active) content as the Ferric Reducing/Antioxidant Power (FRAP) value of over 1000 commonly consumed foods, as well that of many herbs and spices (74,75).…”
Section: Vegetarian Diets and Public Healthmentioning
confidence: 97%
See 1 more Smart Citation
“…10,14,15,17,20,25,60,74,75,111,127,143,155,166,171,172). Halvorsen et al presented the total antioxidant (redox active) content as the Ferric Reducing/Antioxidant Power (FRAP) value of over 1000 commonly consumed foods, as well that of many herbs and spices (74,75).…”
Section: Vegetarian Diets and Public Healthmentioning
confidence: 97%
“…There are various possible explanations for this. Supplementation type, dosage, or duration may have been wrong for the target populations, but supplementation with pure antioxidants cannot reproduce the concerted and varied action of phytochemicals in whole foods (4,18,50,52,105,106,110,129,171). Also, antioxidants can show pro-oxidant activity (71,73,170), and attention is focused increasingly beyond direct antioxidant action and onto multiple and indirect mechanisms, including effects on redox tone (128,144,168,169).…”
Section: Introductionmentioning
confidence: 95%
“…In their study the reported biological and beneficial effects of G. lucidum were investigated using an objective and controlled approach. A previous study by Wachtel-Galor et al (2004a) on the effects of short-term (10 d) supplementation of G. lucidum (using biomarkers of antioxidant status and CHD risk) reported increased antioxidant levels and indicated that this CHM may reduce the risk of CHD. The present study has taken the investigation of G. lucidum further by studying its effects using additional biomarkers of function, namely inflammatory function and immune function; the toxicology of G. lucidum was also investigated by monitoring biomarkers of liver and renal toxicity and genotoxicity.…”
mentioning
confidence: 95%
“…It could be used as an adjuvant in chemotherapy. Lingzhi, a widely used Chinese herb for promoting health, has been tested for antioxidant activity (Wachtel-Galor et al, 2004). A significant post-ingestion increase in plasma antioxidant capacity was seen with slightly increased SOD and GPx activities.…”
Section: Traditional Medicinesmentioning
confidence: 99%